Towards 5G Wireless Networks A Physical Layer Perspective - Khaleghi Bizaki, Hossein (IntechOpen, 2016)
This book intends to provide highlights of the current research topics in the field of 5G and to offer a snapshot of the recent advances and major issues faced today by the researchers in the 5G physical layer perspective. Various aspects of 5G system is deeply discussed (in three parts and ten chapters) with emphasis on its physical layer. Each chapter provides a comprehensive survey of the subject area and ends with a rich list of references to provide an in-depth coverage of the application at hand.